A method for preparing bismuth trioxide-cuprous oxide nanocomposite based on synergistic reaction
Patent Information
- Application Number
- CN202610587972.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-04-29
AI Technical Summary
[0004]但目前公开报道中,尚未发现直接以Bi2O3与Cu2O为双组分构建二元异质结的成熟方法
(1)本发明提供了一种基于协同反应制备Bi2O3-Cu2O纳米复合物的制备技术,首次实现Bi2O3-Cu2O二元异质结的一步水热原位制备;且该方法在同一水热体系中通过氧化还原反应与阴离子交换反应协同进行,促使反应更完全,具有良好原子经济性,符合材料绿色合成要求;
Smart Images

Figure CN122426774B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of nanomaterial preparation and semiconductor photocatalysis, and particularly to a method for preparing bismuth trioxide-cuprous oxide (Bi2O3-Cu2O) nanocomposites based on synergistic reactions. Background Technology
[0002] Bismuth trioxide (Bi2O3) and cuprous oxide (Cu2O) are two important metal oxide semiconductor materials. Both are typical visible light responsive photocatalysts and have good application potential in photocatalytic degradation of organic pollutants and photocatalytic hydrogen production.
[0003] However, single-phase Bi₂O₃ or Cu₂O exhibits significant drawbacks in photocatalysis, with photogenerated carriers readily recombining, leading to low photocatalytic efficiency. Existing research indicates that strategies such as ion doping, heterojunction design, and molecular sensitization can systematically enhance their visible light response and carrier separation efficiency. Specifically, n-type Bi₂O₃ (band gap approximately 2.8 eV) and p-type Cu₂O (band gap approximately 2.1 eV) possess matched band structures, theoretically allowing for the formation of highly efficient pn heterojunctions, significantly enhancing carrier separation efficiency and redox capability.
[0004] However, no mature method for constructing binary heterostructures directly using Bi2O3 and Cu2O as two components has been found in publicly available reports. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a method for preparing Bi2O3-Cu2O nanocomposites based on synergistic reactions. Based on the synergistic effect of redox reaction and anion exchange reaction under the same hydrothermal conditions, high-purity Bi2O3-Cu2O nanocomposites can be prepared in situ in one step without the need for external alkali source and template agent. Moreover, the prepared composite can effectively form pn heterojunctions, significantly inhibit photogenerated carrier recombination, and improve the photocatalytic activity and redox ability of the material. At the same time, the preparation process is simple, green and economical, and easy to industrialize.
[0006] The present invention solves the above-mentioned technical problems by adopting the following technical solutions: A method for preparing Bi₂O₃-Cu₂O nanocomposites based on a synergistic reaction involves dispersing sodium bismuthate, sodium sulfite, and cuprous chloride in deionized water and mixing them thoroughly to obtain a solid-liquid mixture. The solid-liquid mixture is then placed under hydrothermal conditions. Through the synergistic effect of the redox reaction between sodium bismuthate and sodium sulfite, and the anion exchange reaction between cuprous chloride and the hydroxide ions generated in situ, the Bi₂O₃-Cu₂O nanocomposites are prepared in situ in one step. The overall reaction process is as follows: .
[0007] As one of the preferred embodiments of the present invention, the molar ratio of sodium bismuthate, sodium sulfite and cuprous chloride is 1:1:1.
[0008] As one of the preferred embodiments of the present invention, the hydrothermal conditions are: reaction at 180°C for 10-20 hours.
[0009] As one of the preferred embodiments of the present invention, the synergistic reaction under hydrothermal conditions specifically includes the following two simultaneous steps: (1) Redox reaction: Sodium bismuthate and sodium sulfite undergo a redox reaction in a hydrothermal system to produce bismuth trioxide, sodium hydroxide and sodium sulfate. The reaction formula is as follows: ; (2) Anion exchange reaction: The hydroxide ions generated in step (1) undergo anion exchange reaction with cuprous chloride to generate cuprous oxide, as shown in the following reaction formula: .
[0010] As one of the preferred embodiments of the present invention, after the hydrothermal reaction, the steps of centrifugation of the reaction product, washing with deionized water, and drying are further included to finally obtain the Bi2O3-Cu2O nanocomposite described in the present invention.
[0011] As one of the preferred embodiments of the present invention, the drying conditions are: drying at 120°C for 2 hours.
[0012] As one of the preferred embodiments of the present invention, the final Bi2O3-Cu2O nanocomposite has a pn heterojunction structure, wherein the average grain size of Bi2O3 is 43.7~60.3 nm and the average grain size of Cu2O is 8.0~10.7 nm.
[0013] Reaction principle: Solid sodium bismuthate is reduced to Bi₂O₃ by sodium sulfite in aqueous solution, generating hydroxide ions. Under hydrothermal conditions at 180℃, a synergistic anion exchange reaction between solid cuprous chloride and hydroxide ions occurs in the same reaction system, converting cuprous chloride into Cu₂O, which then recombines with Bi₂O₃. The synergistic effect of the redox reaction and the anion exchange reaction ensures the completion of both reactions, ultimately yielding a Bi₂O₃-Cu₂O nanocomposite.
[0014] The advantages of this invention compared to the prior art are: (1) This invention provides a preparation technology for Bi2O3-Cu2O nanocomposites based on synergistic reaction, and realizes the one-step hydrothermal in-situ preparation of Bi2O3-Cu2O binary heterostructure for the first time; and the method promotes more complete reaction by synergistic redox reaction and anion exchange reaction in the same hydrothermal system, which has good atom economy and meets the requirements of green synthesis of materials. (2) This invention does not require the addition of any template agent or alkali. It relies on the redox reaction between sodium bismuthate and sodium sulfite to generate hydroxide ions in situ, forming a self-supplying alkali source system. This ensures the smooth progress of subsequent anion exchange reactions and avoids the introduction of impurities by exogenous alkali, thus obtaining a Bi2O3-Cu2O complex with higher purity and cleaner interface. (3) The composite prepared in this invention has a pn heterojunction structure. The band structures of Bi2O3 (2.8 eV) and Cu2O (2.1 eV) are well matched, which can effectively promote the separation of photogenerated carriers and inhibit recombination, thereby significantly improving the performance of photocatalytic degradation of organic pollutants and photocatalytic hydrogen production, which is superior to single-component materials. At the same time, the average grain size of the obtained Bi2O3 is 43.7~60.3 nm and the average grain size of Cu2O is 8.0~10.7 nm. The grain size is moderate and the distribution is uniform. The interface bonding is high, which further ensures the good photocatalytic stability and reproducibility of the composite, and has practical engineering application value. (4) The preparation method of Bi2O3-Cu2O nanocomposite provided by the present invention is simple and easy to operate. It adopts a single hydrothermal reaction system, the raw materials are cheap and readily available, the reaction conditions are mild, and there is no need for strict preparation conditions and complex post-processing steps. The production cost is low, the environment is friendly, and it is easy to scale up and mass produce industrially. Attached Figure Description
[0015] Figure 1 The image shows a TEM image of the product prepared in Example 2 of the present invention (the scale bar is 100 nm). Figure 2 The XRD patterns of the products prepared in the various embodiments and comparative examples of this invention are shown (with reference to the XRD standard cards of Bi2O3, Cu2O and CuO). Figure 3 The XRD patterns of the product prepared in Comparative Example 1 of this invention, sodium bismuthate and cuprous chloride are shown (with reference to the XRD standard cards of Bi2O3 and Cu2O). Detailed Implementation
[0016] The embodiments of the present invention are described in detail below. These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments. Furthermore, unless otherwise specified, the reagents and experimental methods used in the following embodiments, comparative examples, and experimental examples are all conventional reagents or methods in the art and will not be described again.
[0017] Example 1 This embodiment provides a method for preparing Bi2O3-Cu2O nanocomposites based on a synergistic reaction, comprising the following steps: (1) Add 0.01 mol sodium bismuthate, 0.01 mol sodium sulfite and 0.01 mol cuprous chloride to a 50 ml hydrothermal reactor containing 40 ml deionized water and mix well to obtain a solid-liquid mixture.
[0018] (2) The solid-liquid mixture obtained in step (1) was reacted at 180℃ for 10 h under hydrothermal conditions. Through the synergistic effect of the redox reaction between sodium bismuthate and sodium sulfite in the system, and the anion exchange reaction between cuprous chloride and hydroxide ions generated in situ, Bi2O3-Cu2O nanocomposite was prepared in one step in situ. The synergistic reaction specifically includes the following two steps carried out simultaneously: a. Redox reaction: Sodium bismuthate and sodium sulfite undergo a redox reaction in a hydrothermal system to produce bismuth trioxide, sodium hydroxide, and sodium sulfate. The reaction equation is as follows: ; b. Anion exchange reaction: The hydroxide ions generated in the above redox reaction steps undergo an anion exchange reaction with cuprous chloride to produce cuprous oxide, as shown in the following reaction formula: .
[0019] The entire reaction process is as follows: .
[0020] (3) The reaction product obtained in step (2) is centrifuged, washed with deionized water, and dried at 120°C for 2 hours to obtain the target product Bi2O3-Cu2O nanocomposite.
[0021] Example 2 This embodiment provides a method for preparing Bi2O3-Cu2O nanocomposites based on a synergistic reaction, comprising the following steps: (1) Add 0.01 mol sodium bismuthate, 0.01 mol sodium sulfite and 0.01 mol cuprous chloride to a 50 ml hydrothermal reactor containing 40 ml deionized water and mix well to obtain a solid-liquid mixture.
[0022] (2) The solid-liquid mixture obtained in step (1) was reacted at 180℃ for 15 h under hydrothermal conditions. Through the synergistic effect of the redox reaction between sodium bismuthate and sodium sulfite in the system, and the anion exchange reaction between cuprous chloride and hydroxide ions generated in situ, Bi2O3-Cu2O nanocomposites were prepared in one step in situ. The synergistic reaction specifically included the following two steps carried out simultaneously: a. Redox reaction: Sodium bismuthate and sodium sulfite undergo a redox reaction in a hydrothermal system to produce bismuth trioxide, sodium hydroxide, and sodium sulfate. The reaction equation is as follows: ; b. Anion exchange reaction: The hydroxide ions generated in the above redox reaction steps undergo an anion exchange reaction with cuprous chloride to produce cuprous oxide, as shown in the following reaction formula: .
[0023] The entire reaction process is as follows: .
[0024] (3) The reaction product obtained in step (2) is centrifuged, washed with deionized water, and dried at 120°C for 2 hours to obtain the target product Bi2O3-Cu2O nanocomposite.
[0025] Example 3 This embodiment provides a method for preparing Bi2O3-Cu2O nanocomposites based on a synergistic reaction, comprising the following steps: (1) Add 0.01 mol sodium bismuthate, 0.01 mol sodium sulfite and 0.01 mol cuprous chloride to a 50 ml hydrothermal reactor containing 40 ml deionized water and mix well to obtain a solid-liquid mixture.
[0026] (2) The solid-liquid mixture obtained in step (1) was reacted under hydrothermal conditions at 180℃ for 20 h. Through the synergistic effect of the redox reaction between sodium bismuthate and sodium sulfite in the system, and the anion exchange reaction between cuprous chloride and hydroxide ions generated in situ, Bi2O3-Cu2O nanocomposites were prepared in one step in situ. The synergistic reaction specifically included the following two steps carried out simultaneously: a. Redox reaction: Sodium bismuthate and sodium sulfite undergo a redox reaction in a hydrothermal system to produce bismuth trioxide, sodium hydroxide, and sodium sulfate. The reaction equation is as follows: ; b. Anion exchange reaction: The hydroxide ions generated in the above redox reaction steps undergo an anion exchange reaction with cuprous chloride to produce cuprous oxide, as shown in the following reaction formula: .
[0027] The entire reaction process is as follows: .
[0028] (3) The reaction product obtained in step (2) is centrifuged, washed with deionized water, and dried at 120°C for 2 hours to obtain the target product Bi2O3-Cu2O nanocomposite.
[0029] Comparative Example 1 The preparation method of the bismuth copper-based oxide material in this comparative example is basically the same as that in Example 2. The main difference is that sodium sulfite is not added, so hydroxide ions cannot be generated in situ through redox reaction. The other raw material ratios, hydrothermal conditions (180℃, 15h) and post-processing steps are completely consistent with those in Example 2.
[0030] Comparative Example 2 The preparation method of the bismuth copper-based oxide material in this comparative example is basically the same as that in Example 2. The main difference is that sodium sulfite is not added, but 0.01 mol of sodium hydroxide (equivalent to the amount of hydroxide ions generated in situ in Example 2) is added directly as an exogenous alkali source. The other raw material ratios, hydrothermal conditions (180℃, 15h) and post-treatment steps are completely consistent with those in Example 2.
[0031] Experimental Example 1 The product obtained in the above embodiments (taking Example 2 as an example) was observed under a transmission electron microscope (TEM), and the results are as follows. Figure 1 As shown.
[0032] from Figure 1 It can be seen that the product contains two types of nanoparticles of different sizes: larger Bi2O3 particles are tightly loaded with smaller Cu2O particles on their surface, with good interfacial contact, forming a typical "large particle-small particle" composite structure. Based on common knowledge in the field, Bi2O3 is an n-type semiconductor and Cu2O is a p-type semiconductor; therefore, the prepared Bi2O3-Cu2O nanocomposite has a pn heterojunction structure, with a tight interface between the two, providing a structural basis for efficient separation of photogenerated carriers.
[0033] Experimental Example 2 X-ray diffraction (XRD) analysis was performed on the products obtained in the above examples and comparative examples, as well as the raw materials sodium bismuthate and cuprous chloride. The results are as follows: Figure 2 and Figure 3 As shown.
[0034] Figure 2The XRD patterns of the products prepared in the various embodiments and comparative examples of this invention are shown with reference to the X-ray diffraction standard cards of Bi2O3 (PDF#74-1374), Cu2O (PDF#77-0199), and CuO (PDF#70-6827). Figure 3 The XRD patterns of the product prepared in Comparative Example 1 of this invention, the raw materials sodium bismuthate and cuprous chloride, are shown below, with reference to the X-ray diffraction standard cards for Bi₂O₃ (PDF#74-1374) and Cu₂O (PDF#77-0199). Figure 2 It can be seen that the diffraction peak positions of the products obtained in Examples 1-3 of this invention correspond completely to the diffraction peak positions of standard Bi2O3 and Cu2O, with no impurity peaks appearing, indicating that the products are Bi2O3-Cu2O nanocomposites with good crystallinity and high purity. Comparative Example 2 did not show obvious Cu2O characteristic diffraction peaks, but it did show weak CuO diffraction peaks and many other unknown diffraction peaks. This is likely due to the further oxidation of the product generated by the reaction of cuprous chloride and sodium hydroxide in the presence of sodium bismuthate, a pentavalent bismuth salt oxidant. This indicates that even with the addition of sodium hydroxide as an exogenous alkali source, Cu2O cannot be obtained without the synergistic reduction of pentavalent bismuth to trivalent bismuth by sodium sulfite. Figure 3 It can be seen that Comparative Example 1 did not show obvious characteristic diffraction peaks of Cu2O and Bi2O3. Only obvious diffraction peaks of the raw materials cuprous chloride and sodium bismuthate, as well as weaker diffraction peaks of other unknown substances, were observed. This indicates that in the absence of sodium sulfite, hydroxide ions cannot be generated in situ, and the synergistic reaction of redox reaction and anion exchange reaction in the system cannot occur, making it difficult to generate Bi2O3 and Cu2O and achieve composite formation. The above results prove that the present invention, through the synergistic reaction strategy of in-situ alkali production, can prepare Bi2O3-Cu2O nanocomposites with high crystallinity, pure phase, and good interfacial bonding, which cannot be achieved in the comparative example.
[0035] Furthermore, based on the XRD patterns of the products from Examples 1, 2, and 3, and using the Scherrer formula for calculation, the average grain sizes of Bi₂O₃ in the products from Examples 1, 2, and 3 were 43.7 nm, 52.5 nm, and 60.3 nm, respectively, and the average grain sizes of Cu₂O were 8.0 nm, 9.5 nm, and 10.7 nm, respectively. This indicates that as the reaction time increases, the average grain sizes of both Bi₂O₃ and Cu₂O in the products gradually increase, with the increase in Bi₂O₃ being more significant. This demonstrates that under the conditions of this invention, the grain size of the products can be effectively controlled by adjusting the hydrothermal time.
[0036] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing bismuth trioxide-cuprous oxide nanocomposites based on a synergistic reaction, characterized in that, Sodium bismuthate, sodium sulfite, and cuprous chloride were dispersed in deionized water at a molar ratio of 1:1:1 and mixed thoroughly to obtain a solid-liquid mixture. The solid-liquid mixture was then placed under hydrothermal conditions at 180℃ for 10–20 h. Through the synergistic effect of the redox reaction between sodium bismuthate and sodium sulfite, and the anion exchange reaction between cuprous chloride and the hydroxide ions generated in situ, a Bi₂O₃-Cu₂O nanocomposite was prepared in one step in situ. The overall reaction process is as follows: 。 2. The method according to claim 1, characterized in that, The synergistic reaction under hydrothermal conditions specifically includes the following two simultaneous steps: (1) Redox reaction: Sodium bismuthate and sodium sulfite undergo a redox reaction in a hydrothermal system to produce bismuth trioxide, sodium hydroxide and sodium sulfate. The reaction formula is as follows: ; (2) Anion exchange reaction: The hydroxide ions generated in step (1) undergo anion exchange reaction with cuprous chloride to generate cuprous oxide, as shown in the following reaction formula: 。 3. The method according to claim 1 or 2, characterized in that, After the hydrothermal reaction, the process also includes centrifugation of the reaction products, washing with deionized water, and drying, ultimately obtaining the Bi2O3-Cu2O nanocomposite.
4. The method according to claim 3, characterized in that, The drying conditions are: drying at 120℃ for 2 hours.
5. The method according to claim 3, characterized in that, The resulting Bi2O3-Cu2O nanocomposite has a pn heterojunction structure, with the average grain size of Bi2O3 being 43.7~60.3 nm and the average grain size of Cu2O being 8.0~10.7 nm.
Citation Information
Patent Citations
Preparation method of bismuth trioxide nanosphere
CN104801294A
Cu2O-Bi2O3 composite material with photocatalytic performance and preparation method thereof
CN116251598A